Monitoring the effectiveness of surgical handwashing in healthcare workers of a fourth level operating room using bioluminescence assays - Vaca González, Juan Jairo; Ramírez Espinosa, Claudia Marcela; Guayan Ardila, Ingrid Carolina; Serrano Riaño, Julieth Yadira; Torres Gil, Diana Paola (Ingeniería Solidaria, 2022)
Aims: To assesses the effectiveness of surgical handwashing (S-HW) in healthcare workers (HCWs) in terms of organic material and bacteria elimination by means of bioluminescence assays. Methods: 62-HCWs were subjected to bioluminescence analyses to determine adenosine triphosphate (ATP) and colony forming units (CFU) of Enterobacteriaceae (EB) and E. coli before and after S-HW. A checklist to evaluate adherence to hand hygiene (HH) protocol was implemented. Results: ATP before HH (510.9/RLU) was reduced after S-HW (54.6/RLU), evidencing a significant decrease (p=0.001). Regarding the bacteria, 26.6/CFU and 4/CFU for EB and E. coli were reported before S-HW, respectively. After S-HW, CFU decreased for EB (21.8/CFU) and E. coli (3.5/CFU) without showing a significant reduction (p=0.679). Low ATP did not evidence a direct relation with EB (p=0.082) and E. coli (p=0.680) reduction. Surgical instrument professionals (p=0.001), general surgeons (p=0.001), residents (p=0.017), orthopedists (p=0.029) and otolaryngologists (p=0.029) evidenced a reduction in ATP after S-HW. Factors such as S-HW direction, surgical soap, moments and time of S-HW implemented showed a statistically significant difference in reduction of ATP, but not in CFU. Conclusion: Although there was a reduction in elimination of ATP, there was no evidence of a decrease in bacteria. This finding not only allowed to identify potential errors in S-HW processes, but also permitted to generate strategies to improve HH to prevent healthcare-associated infections.